A9.15 Higher disease damage among african americans with familial versus sporadic systemic lupus erythematosus. (31st January 2014) - Barnado, April; Wheless, Lee; Slan, Stephanie; Gilkeson, Gary S; Kamen, Diane L
Abstract : Background: Studies in Caucasian cohorts have found no significant clinical or serologic differences in systemic lupus erythematosus (SLE) patients with a family history of SLE compared to those with no family history. Using a unique cohort of African Americans with SLE and a high prevalence of multipatient families, we examined whether having a family history of SLE would impact autoantibodies, age at SLE diagnosis, ACR criteria, and disease damage. Methods: Utilizing data from a cohort of African Americans with SLE, familial SLE was defined as having a confirmed family history of SLE versus sporadic SLE defined as no known family history of SLE. SSA, SSB, ds-DNA, anticardiolipin, and lupus anticoagulant were tested. Cumulative damage was measured using the Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SDI). Chi-square testing was used for comparing categorical and Student's t-test used for comparing continuous variables. The association between familial vs. sporadic SLE and SDI was modeled using Poisson regression adjusting for covariates. Two-sided p-values < 0.05 were significant. Results: 400 African American females had SLE, 55 of who were familial SLE cases. Mean age of familial cases was 47.1 + 13.9 years vs. 43.3 + 14.7 for sporadic cases (p = 0.08). Mean age at diagnosis was 28.1 + 11.5 years for familial vs. 31.0 + 13.0 for sporadic (p = 0.13). Mean disease duration was 18.7 + 9.1 years for familial vs. 12.3 + 7.1 for sporadic (p < 0.01). Familial SLE cases had similar rates of dsDNA, SSA, SSB, anticardiolipin, and lupus anticoagulant positivity compared to sporadic cases. Familial cases had similar rates of being on dialysis as sporadic cases. Familial cases were significantly more likely to fulfill ACR criterion of photosensitivity (65.3% vs. 49.3%, p = 0.04) but no significant differences in the other ACR criteria. Familial cases had significantly higher SDI scores (2.8 + 2.6 vs. 1.6 + 1.8, p = 0.02) compared to sporadic cases. After adjustment for age at diagnosis and disease duration, familial SLE was still associated with a significantly higher SDI (p < 0.01). Conclusion: Consistent with Caucasian SLE cohorts, we found African American SLE familial and sporadic cases had similar serologic and clinical profiles. However, familial SLE cases had significantly higher SDI scores compared to sporadic cases, even after adjusting for age at diagnosis and disease duration. Further studies are underway to elucidate the causes of higher disease damage in familial versus sporadic SLE.